Ejercicios de estática - Martínez Martínez, Jaime; Miranda Cordero, Lorenzo O.; Torres Ortíz, Lanzier E.; Solar González, Jorge (Facultad de Ingeniería, 2002)
EJERCICIOS DE ESTÁTICA
EJERCICIOS DE ESTÁTICA
Keywords: Estática; Ingeniería; Ejercicios